ANALISA STABILITAS PERKUATAN LERENG TEBING SUNGAI (REVETMENT) PADA HULU SUNGAI BENGAWAN SOLO - , FATHUL MUNGIN G P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Revetment has a crucial role to protect the stability of slopes as defense against the risk of disrepair caused by strong forces like the role of revetment at Gajah Mungkur reservoir, Bengawan Solo river. The analysis to investigate the level of revetment stability to hold the load and forces which are the risk of disrepair is absolutely needed. This study aimed to analyze the stability of the structure of revetment at Bengawan Solo river in holding the forces working againts the slopes. By this analysis, it could be determined the effect of the applied revetment. This study used numerical calculation with Coulomb and Mononobe Okabe theories to examine the strength of the soil. Then it was further analyzed using Element method and Plaxis program to find the safety rate . The result of the analysis showed that the structure has stability level categorized as good and it could protect the slopes againts assumed forces.